5-lipoxygenase-dependent biosynthesis of novel 20:4 n-3 metabolites with anti-inflammatory activity. (November 2018) - Gagnon, K.J.; Lefort, N.; Poirier, S.J.; Barnett, D.A.; Surette, M.E.
Highlights: 5-lipoxygenase (5-LO) catalyzes the conversion of 20:4 n-3 into novel oxygenated metabolites. Metabolites identified as Δ 17 -8‑hydroxy‑eicosatetraenoic acid (Δ 17 -8-HETE) and Δ 17 -8, 15-dihydroxy-eicosatetraenoic acid (Δ 17 -8, 15-diHETE). Δ 17 -8, 15-diHETE biosynthesis is inhibited by LTA4 hydrolase inhibitor SC 57461A. Δ 17 -8, 15-diHETE inhibits arachidonic acid-induced autocrine neutrophil stimulation and LTB4 -induced neutrophil chemotaxis. Abstract: 5-lipoxygenase (5-LO) catalyzes the conversion of arachidonic acid (AA) into pro-inflammatory leukotrienes. N-3 PUFA like eicosapentaenoic acid are subject to a similar metabolism and are precursors of pro-resolving mediators. Stearidonic acid (18:4 n-3, SDA) is a plant source of n-3 PUFA that is elongated to 20:4 n-3, an analogue of AA. However, no 5-LO metabolites of 20:4 n-3 have been reported. In this study, control and 5-LO-expressing HEK293 cells were stimulated in the presence of 20:4 n-3. Metabolites were characterized by LC-MS/MS and their anti-inflammatory properties assessed using AA-induced autocrine neutrophil stimulation and leukotriene B4 -mediated chemotaxis. 8‑hydroxy‑9, 11, 14, 17-eicosatetraenoic acid (Δ 17 -8-HETE) and 8, 15-dihydroxy-9, 11, 13, 17-eicosatetraenoic acid (Δ 17 -8, 15-diHETE) were identified as novel metabolites. Δ 17 -8, 15-diHETE production was inhibited by the leukotriene A4 hydrolase inhibitor SC 57461A. Autocrine neutrophil leukotriene stimulation and neutrophil chemotaxis, both BLT1-dependent processes, were inhibited by Δ 17 -8, 15-diHETE at low nM concentrations. These data support an anti-inflammatory role for Δ 17 -8, 15-diHETE, a novel 5-LO product.